Selection of indigenous starter culture for safety and its effect on reduction of biogenic amine content in Moo som - Pussadee Tangwatcharin; Jiraroj Nithisantawakhup; Supaluk Sorapukdee (My University, 2019)
Objective The aims of this study were to select one strain of Lactobacillus plantarum (L. plantarum) for a potential indigenous safe starter culture with low level antibiotic resistant and low biogenic amine production and evaluate its effect on biogenic amines reduction in Moo som. Methods Three strains of indigenous L. plantarum starter culture (KL101, KL102, and KL103) were selected based on their safety including antibiotic resistance and decarboxylase activity, and fermentation property as compared with a commercial starter culture (L. plantarum TISIR543). Subsequently, the effect of the selected indigenous safe starter culture on biogenic amines formation during Moo som fermentation was studied. Results KL102 and TISIR 543 were susceptible to penicillin G, tetracycline, chloramphenicol, erythromycin, gentamycin, streptomycin, vancomycin, ciprofloxacin and trimethoprim (MIC90 ranging from 0.25 to 4 μg/mL). All strains were negative amino acid-decarboxylase for lysis of biogenic amines in screening medium. For fermentation in Moo som broth, a relatively high maximum growth rate of KL102 and TISIR543 resulted in a generation time than in the other strains (p<0.05). These strain counts were constant during the end of fermentation. Similarly, KL102 or TISIR543 addition supported increases of lactic acid bacterial count and total acidity in Moo som fermentation. For biogenic amine reduction, tyramine, putrescine, histamine and spermine contents in Moo som decreased significantly by the addition KL102 during 1 d of fermentation (p<0.05). In final product, histamine, spermine and tryptamine contents in Moo som inoculated with KL102 were lower amount those with TISIR543 (p<0.05). Conclusion KL102 was a suitable starter culture to reduce the biogenic amine formation in Moo som. Keywords: Lactic Acid Bacteria Starter Culture; Lactobacillus plantarum; Antibiotic Resistance; Biogenic Amine; Moo som; Traditional Thai Fermented Pork
Keywords: Starter; Indigenous culture; Content (measure theory); Polyamine Metabolism and Applications